2012
DOI: 10.1007/s10620-012-2468-x
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning of Obese Patients for Colonoscopy Results in Shortened Cecal Intubation Times: A Randomized Trial

Abstract: Performance of colonoscopy in the prone position for obese patients results in significantly shorter cecal intubation times and decreased need for patient repositioning. Prone positioning is well accepted and does not significantly increase procedure-related discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Previous studies have shown that an ~20% diff erence in procedure time can be achieved by a change in starting position ( 3 ). Mean time to reach the cecum has been reported as 6.4 min with s.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that an ~20% diff erence in procedure time can be achieved by a change in starting position ( 3 ). Mean time to reach the cecum has been reported as 6.4 min with s.d.…”
Section: Discussionmentioning
confidence: 99%
“…Uddin et al ( 3 ) conducted a randomized trial of obese patients and found benefi t in starting the procedure in the prone position compared with LL positions. No trial to date has compared right with left -sided positioning with respect to cecal intubation time or patient comfort.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in which abdominal compression obtained with a fitted corset facilitates colonoscopy reported that extra abdominal compression and a change of position was used less frequently in the study subjects accompanied by less procedural pain [21]. In contrast, no definite data are available on the effect of a change from standard left lateral decubitus to prone position in facilitating colonoscopy in obese patients.This number of Digestive Diseases and Sciences includes a prospective randomized trial by Uddin and colleagues [22] which reports for the first time that starting sedated colonoscopy in prone position for male obese subjects (BMI [ 30 kg/ m 2 ) significantly shortens cecal intubation times with less need for patient repositioning. Additionally, the authors reported no differences in subjects' perception of pain or their willingness to repeat the procedure when compared with obese subjects in whom the exploration was started using the standard left decubitus position.…”
mentioning
confidence: 99%
“…This number of Digestive Diseases and Sciences includes a prospective randomized trial by Uddin and colleagues [22] which reports for the first time that starting sedated colonoscopy in prone position for male obese subjects (BMI [ 30 kg/ m 2 ) significantly shortens cecal intubation times with less need for patient repositioning. Additionally, the authors reported no differences in subjects' perception of pain or their willingness to repeat the procedure when compared with obese subjects in whom the exploration was started using the standard left decubitus position.…”
mentioning
confidence: 99%
See 1 more Smart Citation